Comparative study of qualitative and quantitative antigen tests using SARS-CoV-2 isolates - SADAMASU, Kenji; KITAMURA, Yurie; KAWAKAMI, Mamiyo; YOSHIDA, Isao; NAGASHIMA, Mami; FUJIWARA, Takushi; ITO, Hitoshi (Japanese Journal of Medical Technology, 2024)
Purpose: SARS-CoV-2 has spread in Japan since January 2020 and has mutated repeatedly, resulting in shifts in the dominant circulating strains. To clarify the usefulness of antigen testing for mutant strains, we compared qualitative and quantitative antigen tests using different SARS-CoV-2 isolates. Methods: Culture supernatants of Delta (AY.54) and Omicron (BA.2, BA.4, and BA.5.2) variants isolated in Vero E6/TMPRSS2 cells were used as samples. Dilution series were prepared from the samples using PBS (−) and performed according to the package insert of each test kit and reagent. Results: The quantitative test tended to have better detection sensitivity than the qualitative tests, although some qualitative tests had comparable detection sensitivity to the quantitative test. The detection sensitivities of the tests ranged 105–106 copies/40 μL. The detection sensitivities of the test did not differ among the variant strains. Conclusion: Although differences in detection sensitivity were observed among the tests, all kits could detect high viral loads. There was little difference in detection sensitivity between the different mutant strains, indicating that the antigen test method is also valid for Omicron variants.